The Effect of Unripe Dates (Phoenix dactylifera) on Rat Ovarian Follicle Maturation and Ovulation - Herlambang, Herlambang; Rahman, Ave Olivia; Kusdiyah, Erny (Fakultas Kedokteran Universitas Brawijaya, 2020)
Unripe dates are believed by Indonesian citizens to increase fertility. This study aimed to assess the effect of unripe dates in the ovary of rats. Fresh yellow-colored dates were dried in an oven and crushed into powder. Eighteen rats aged three months and had given birth once were randomly divided into three groups. The treatment groups were given unripe dates at doses of 160mg/kgBW and 320mg/kgBW through a feeding tube for 28 days, and the control group was only given distilled water. Histopathological examination was carried out by the pathology expert using Hematoxylin-Eosin staining to observe the number of ovarian follicles according to their maturation stage. The results showed that the administration of unripe dates powder 320mg/kgBW increased corpus luteum number (21.50Â±4.72) and was statistically significant compared to the control group (15.16Â±3.71). Similar differences were also found in other stages of the follicle although not statistically significant. Administration of unripe date powder can increase ovulation induction among fertile rats.